Humanistic Education in the Dayah Teaching System in Aceh - Idris, Tasnim; Nurbayani; Mutia, Jarah; Rijal, Fakhrul; Furqan, Muhammad (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
This research aims to find the value of humanist education contained in the Dayah Salafiyah learning system in Aceh, how it is implemented and what factors hinder and support the implementation of humanist education in Dayah Salafiyah in Aceh. This study uses a qualitative method. Naturalistic Approach, Phenomenological Approach, Ethnographic Approach. After conducting research, the author found the following results, firstly, the value of humanism in the Dayah Salafiyah learning system is religious humanism based on local wisdom. Religious humanism based on local wisdom is built on religious values and local wisdom. The value of humanistic education is the value of freedom which is tied to religious values, the value of equality and always being together in carrying out activities, brotherhood which is built based on local wisdom without looking at ethnicity and region, helping each other and caring for each other, being independent and mutual honor. Second, the implementation of humanist education in the learning system at Dayah Salafiyah in Aceh is Humanism Based on Tafa'ul 'Amali wa al-Ta'abbudi which is found in the aspects of educational objectives, educational materials and educational aspects which are oriented towards strengthening good deeds in order to build hablum minallah and hablum minannas. Humanistic education in Dayah humanism based on Tafa'ul 'Amali wa al-Ta'abbudi forms an attitude of helping each other, helps each other and strives to realize rabbani humans as 'abdullah and khalifatullah on the face of the earth. Third, there are supporting and inhibiting factors in efforts to implement humanist education in Dayah Salafiyah in Aceh. The supporting factors are a spiritually based educational orientation, a patron-client relationship pattern based on mu'amalah ma'a al-nas, extrinsic motivation based on advice, affordable educational costs. Meanwhile, the inhibiting factors are limited educational facilities, education cannot yet follow science and technology, the educational curriculum is static.